MITIGASI HOAX DI ERA DISRUPSI MELALUI LITERASI DIGITAL - Gema Irhamdhika (Jurnal Ilmu Komunikasi (J-IKA), 2022)
AbstractThis study discusses efforts to ward off hoaxes in the era of disruption through digital literacy. In this sophisticated era of disruption, hoax information or fake news is circulating in people's lives. Hoax information can divide society because it is misleading, so this needs to be addressed. In this case, digital literacy can be a solution to mitigate hoaxes with the aim of creating critical power. The research method discussed is a qualitative method with a literature study approach. The conclusion is that the aspect of developing digital literacy can be done strategically through digital literacy learning for schools, families, and communities. The greater the digital literacy ability they have, the greater the critical power they have.Keywords: hoax, disruption, digital literacy, internet, information